2009
DOI: 10.1080/09553000902993908
|View full text |Cite
|
Sign up to set email alerts
|

Static magnetic field attenuates mortality rate of mice by increasing the production of IL-1 receptor antagonist

Abstract: Exposure to an SMF increases the plasma levels of IL-1ra. This effect may inhibit the reduction in PLT in plasma, resulting in prevention in LPS induced DIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…However, an interesting observation from the present study is that body temperature does not increase in response to LPS when mice are pre-exposed to an SMF (Figure 4). Combining this observation with the findings shown in Figure 3 which demonstrate that the LPS-induced mortality rate in mice treated with SMF was significantly reduced, confirmed the results of previous reports that SMF exposure has an attenuating effect on mortality in response to LPS challenge in mice (Lin et al 2009, Shen et al 2014). Since no demonstrable effects of moderate without the LPS-challenge did not increase the thickness of the alveolar wall ( Figure 5b).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, an interesting observation from the present study is that body temperature does not increase in response to LPS when mice are pre-exposed to an SMF (Figure 4). Combining this observation with the findings shown in Figure 3 which demonstrate that the LPS-induced mortality rate in mice treated with SMF was significantly reduced, confirmed the results of previous reports that SMF exposure has an attenuating effect on mortality in response to LPS challenge in mice (Lin et al 2009, Shen et al 2014). Since no demonstrable effects of moderate without the LPS-challenge did not increase the thickness of the alveolar wall ( Figure 5b).…”
Section: Discussionsupporting
confidence: 94%
“…Survival of bacterial infection among patients with MOF is improved by shutting down or controlling the septic response using antiendotoxin therapy (Deitch 1992, Balk 2000, Nguyen et al 2006). Since previous reports indicate that exposure to SMF increases the plasma levels of IL-1ra (Lin et al 2008(Lin et al , 2009), (2014) also proposed that pretreatment with SMF reduced LPS-induced neurodegenerative processes by inhibiting reactive oxygen species-induced neural tissue and neural cell damage.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, exposure to SMF increased blood glucose and decreased insulin release leading to a diabetic-like state in pregnant rats (Chater et al 2006). The effect of SMF on the survival rate of LPS (lipopoly-saccharide)-induced male BALB/cByJ mice was tested (Lin et al 2009). Mice were exposed to 0.25 T SMF for 2 h before LPS injection.…”
Section: Effect Of Smf On Body Weightmentioning
confidence: 99%
“…Studies with acute peripheral [39], visceral [14] inflammation or even chronic neuropathy [15] showed that SMF-exposure contributes to the machinery of the mammalian body to recover from inflammation. Mice with induced disseminated intravascular coagulation showed lower mortality rate if exposed to SMF [40].…”
Section: Animal Experimentsmentioning
confidence: 99%